Sagot :
RADICALS
==============================
[tex] \tt \large 42) \: \green{\Large{C}}\begin{cases} \: \sf \sqrt{x} = 10 \\ \: \sf {( \sqrt{x}) }^{2} = {10}^{2} \\ \: \sf x = 100 \end{cases}[/tex]
[tex]\tt \large 43) \: \green{\Large{C}}\begin{cases} \: \sf - 5\sqrt{b} = - 50 \\ \: \sf \frac{ - 5 \sqrt{b} }{ - 5} = \frac{ - 50}{ - 5} \\ \: \sf \sqrt{b} = 10 \\ \: \sf {( \sqrt{b} )}^{2} = {10}^{2} \\ \: \sf b = 100 \end{cases}[/tex]
[tex]\tt \large 44) \: \green{\Large{A}}\begin{cases} \: \sf \sqrt[4]{2m} = 4 \\ \: \sf {( \sqrt[4]{2m} )}^{4} = {4}^{4} \\ \: \sf2m = 256 \\ \: \sf \frac{2m}{2} = \frac{256}{2} \\ \: \sf m = 128 \end{cases}[/tex]
[tex]\tt \large 45) \: \green{\Large{A}}\begin{cases} \: \sf \sqrt{x - 1} = x - 7 \\ \: \sf {( \sqrt{x - 1} )}^{2} = {(x - 7)}^{2} \\ \: \sf x - 1 = {x}^{2} - 14x + 49 \\ \: \sf - {x}^{2} + 14x + x = 49 + 1 \\ \: \sf - {x}^{2} + 15x = 50 \\ \: \sf {x}^{2} - 15 + 50 = 0 \\ \: \sf(x - 5)(x - 10) = 0 \\ \: \sf x - 10 = 0 \\ \: \sf x = 10 \end{cases}[/tex]
==============================
#CarryOnLearning
(ノ^_^)ノ